High glucose–induced ubiquitination of G6PD leads to the injury of podocytes. Issue 5 (20th February 2019) - Wang, Meng; Hu, Ji; Yan, Linling; Yang, Yeping; He, Min; Wu, Meng; Li, Qin; Gong, Wei; Yang, Yang; Wang, Yi; Handy, Diane E.; Lu, Bin; et al.
ABSTRACT: Oxidative stress contributes substantially to podocyte injury, which plays an important role in the development of diabetic kidney disease. The mechanism of hyperglycemia‐induced oxidative stress in podocytes is not fully understood. Glucose‐6‐phosphate dehydrogenase (G6PD) is critical in maintaining NADPH, which is an important cofactor for the antioxidant system. Here, we hypothesized that high glucose induced ubiquitination and degradation of G6PD, which injured podocytes by reactive oxygen species (ROS) accumulation. We found that G6PD protein expression was decreased in kidneys of both diabetic patients and diabetic rodents. G6PD activity was also reduced in diabetic mice. Overexpressing G6PD reversed redox imbalance and podocyte apoptosis induced by high glucose and palmitate. Inhibition of G6PD with small interfering RNA induced podocyte apoptosis. In kidneys of G6PD‐deficient mice, podocyte apoptosis was significantly increased. Interestingly, high glucose had no effect on G6PD mRNA expression. Decreased G6PD protein expression was mediated by the ubiquitin proteasome pathway. We found that the von Hippel–Lindau (VHL) protein, an E3 ubiquitin ligase subunit, directly bound to G6PD and degraded G6PD through ubiquitylating G6PD on K 366 and K 403 . In summary, our data suggest that high glucose induces ubiquitination of G6PD by VHL E3 ubiquitin ligase, which leads to ROS accumulation and podocyte injury.—Wang, M., Hu, J., Yan, L., Yang, Y., He, M., Wu, M., Li, Q., Gong, W., Yang, Y., Wang, Y., Handy, D. E., Lu, B., Hao, C., Wang, Q., Li, Y., Hu, R., Stanton, R. C., Zhang, Z. High glucose—induced ubiquitination of G6PD leads to the injury of podocytes. FASEB J. 33, 6296–6310 (2019). www.fasebj.org